Temporariness of textile architecture. A comparitive study on innovation - Carlotta Mazzola; Alessandro Liuti (Agathón)
Due to the increasing demand in temporary and adaptable city spaces, this article discusses international projects and prototypes built in the emerging field of temporary textile architecture. On the one hand, these structures negotiate temporary, contextual, and functional requisites from early design stages; on the other, they wisely blend typological, technological, and constructive features. The discussion pivots around the tight link between architectural and technological innovation, and how this often generates improvements in functional and environmental performances while enabling a more conscious resource allocation throughout the lifespan of a project.